Repo funding and internal capital markets in the financial crisis - Cornelia Düwel (Deutsche Bundesbank, 2013)
This paper examines how the exposure of German parent banks to the disruptions on sale and repurchase markets (repo markets) during the financial crisis has affected their provision of funds to their foreign branches and subsidiaries via bank-internal capital markets. The collapse of the subprime market, the rescue of Bear Stearns and the bankruptcy of Lehman Brothers are analyzed with regard to their role as amplifiers of uncertainty about the value of collateral used in repo transactions and mistrust among market participants. The results show that parent banks which were more exposed to these disruptions were more likely to withdraw bank-internal funds from their branches and subsidiaries located abroad. Among the three events, the rescue of Bear Stearns triggered the largest contraction on internal capital markets from the part of the parent bank, possibly because this event demonstrated for the first time the fragility of even very large financial institutions. After the subprime market collapse, branches were briefly more protected as core investment locations, while subsidiaries were used as core funding locations up to the Lehman Brothers bankruptcy. All in all, funding via repo markets is found to be one channel that transmitted shocks primarily related to the US financial system abroad.
Keywords: G21; G15; F34; E44; 330; repo; funding structure; multinational banks; internal capital market; intra-bank lending; financial crisis